2017
DOI: 10.1017/jfm.2017.707
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning of cross-flow instability modes using dielectric barrier discharge plasma actuators

Abstract: In the current study, selective forcing of cross-flow instability modes evolving on a 45• swept wing at Re = 2.17 · 10 6 is achieved by means of spanwise-modulated plasma actuators, positioned near the leading edge. In the perspective of laminar flow control, the followed methodology holds on the discrete roughness elements/upstream flow deformation (DRE/UFD) approach, thoroughly investigated by e.g. Saric et al. (1998);Malik et al. (1999) and Wassermann & Kloker (2002). The possibility of using active devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 54 publications
(186 reference statements)
7
60
0
3
Order By: Relevance
“…The swept-wing model features an in-house designed airfoil shape (66018M3J ), streamwise chord of 1.27m and a 45 • sweep. Details of the employed swept-wing model and the wind tunnel are given in Serpieri & Kotsonis (2016) and Serpieri et al (2017). The flow over the wing's pressure side was investigated.…”
Section: Experimental Setup and Measurement Techniquementioning
confidence: 99%
See 4 more Smart Citations
“…The swept-wing model features an in-house designed airfoil shape (66018M3J ), streamwise chord of 1.27m and a 45 • sweep. Details of the employed swept-wing model and the wind tunnel are given in Serpieri & Kotsonis (2016) and Serpieri et al (2017). The flow over the wing's pressure side was investigated.…”
Section: Experimental Setup and Measurement Techniquementioning
confidence: 99%
“…Different strategies have been proposed and investigated to control transition induced by stationary CFI modes. A brief review of these can be found in Serpieri et al (2017). A strategy that has received considerable attention is the use of discrete roughness elements (DRE), first proposed by Saric and co-workers (see Saric et al (2003)) and later generalised as upstream flow deformation (UFD) by Wassermann & Kloker (2002).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations